The Political Economy of Bank Regulation in Developing Countries : Risk and Reputation - Jones, Emily; Jones, Emily (Oxford Oxford University Press, 2020)
Why do governments in some developing countries implement international standards, while others do not? Focusing on the politics of bank regulation, this book develops a new framework to explain regulatory interdependence between countries in the core and the periphery of the global financial system. Drawing on in-depth analysis of eleven countries across Africa, Asia, and Latin America, it shows how financial globalization generates strong reputational and competitive incentives for developing countries to converge on international standards. Regulatory interdependence is generated by relations between regulators, politicians, and banks within developing countries, and international actors including investors, peer regulators, and international financial institutions. We explain why it is that some configurations of domestic politics and forms of integration into global finance generate convergence with international standards, while other configurations lead to divergence. This book contributes to our understanding of the ways in which governments and firms in the core of global finance powerfully shape regulatory politics in the periphery, and the ways in which peripheral governments and firms manoeuvre within the constraints and opportunities created by financial globalization
English
Keywords: Political science & theory; Political economy; Comparative politics; Development studies; Development economics & emerging economies; Africa; Asia; Latin America; financial globalization; regulatory interdependence; international banking standards; Basel I; Basel II; Basel III; transnational policy networks